Rossby Wave Changes During the Recent Decades in Mid-Latitude Continents in the Northern Hemisphere - Juskenaite, Ieva (UiT The Arctic University of Norway, 2022)
Increasing frequency and severity of extreme weather events throughout the recent years is a highly concerning topic. Extreme and unusual weather conditions, such as heat waves, floods and cold spells are causing a major concern for humanity. Agricultural changes, damages in infrastructure and the loss of human lives are some of the extreme weather event consequences, with the most drastic consequences experienced by the poor and least adaptable groups of society. Recent studies indicate that the increase of extreme weather events can be linked to the effects of global warming, and projections indicate that the frequency and severity of these events is expected to continue increasing in the nearest future. Extreme weather events in mid-latitude continents in the Northern Hemisphere are considered to be linked to atmospheric circulation changes, that are induced by the decreasing meridional temperature gradient due to the effects of Arctic amplification. Atmospheric Rossby waves, in addition to baroclinic cyclones, are considered to be the main factors driving the atmospheric mid-latitude circulation, and recent studies suggest that changes in phase velocity and amplitude of Rossby waves is a indirect consequence of climate change. Here, an attempt to analyse the changes in atmospheric wave amplitudes throughout the recent decades is presented, concentrating on the amplitude tendencies regarding the most extreme amplitude anomalies. This is accomplished by applying Fourier decomposition on a geopotential height field, splitting it into planetary- and synoptic-scaled waves, and further analysing the amplitude changes and tendencies regarding the planetary-scaled Rossby waves. Throughout this studies, no certain amplitude tendencies could be confirmed when regarding all of the planetary waves together, however potential linearly increasing amplitude tendencies could be noted when performing individual Rossby wave analysis.